Can Ketogenic Diet Improve Alzheimer's Disease? Association With Anxiety, Depression, and Glutamate System - de la Rubia Ortí, Jose Enrique; Fernández, David; Platero, Félix; García-Pardo, María Pilar (Frontiers in Nutrition, 2021)
Background: Alzheimer's disease is the most common neurodegenerative disorder in our society, mainly characterized by loss of cognitive function. However, other symptoms such as anxiety and depression have been described in patients. The process is mediated by alterations in the synaptic and extrasynaptic activity of the neurotransmitter glutamate, which are linked to a hypometabolism of glucose as the main source of brain energy. In that respect, Ketogenic diet (KD) has been proposed as a non-pharmacological treatment serving as an alternative energy source to the neurons increasing the fat percentage and reducing the carbohydrates percentage, showing promising results to improve the cognitive symptoms associated with different neurodegenerative disorders, including AD. However, the association of this type of diet with emotional symptoms and the modulation of glutamate neurotransmission systems after this dietary reduction of carbohydrates are unknown. Objective: The aim of this short review is to provide update studies and discuss about the relationship between KD, anxiety, depression, and glutamate activity in AD patients. Discussion: The main results suggest that the KD is an alternative energy source for neurons in AD with positive consequences for the brain at different levels such as epigenetic, metabolic and signaling, and that the substitution of carbohydrates for fats is also associated with emotional symptoms and glutamate activity in AD.